Scaling up Agricultural Technologies - Linn, Johannes F. (2014)
"Scaling up Agricultural Technologies" by Johannes F. Linn, Emerging Markets Forum and Brookings. Presented at Food Security in a World of Growing Natural Resource Scarcity event hosted by IFPRI on February 12, 2014.